Intravascular haemolysis during prolonged running on asphalt and natural grass in long and middle distance runners - Janakiraman, K.; Shenoy, S.; Sandhu, J. S. (Journal of Sports Sciences, 2011)
Surface features such as uneven playing surfaces, low impact absorption capacity and inappropriate friction/traction characteristics are connected with injury prevalence whereas force impact during foot strike has been suggested to be an important mechanism of intravascular haemolysis during running. We aimed to evaluate intravascular haemolysis during running and compare the effect of running on two different types of surfaces on haemolysis. We selected two surfaces (asphalt and grass) on which these athletes usually run. Participants were randomly assigned to group A (asphalt) or group B (grass) with 10 athletes in each group. Each athlete completed one hour of running at the calculated target heart rate (60-70%). Venous blood samples were collected before and immediately after running. We measured unconjugated bilirubin (UBR) (mg/dl), lactate dehydrogenase (LDH) (µ/ml), haemoglobin (g/l) and serum ferritin (ng/ml) as indicators of haemolysis. Athletes who ran on grass demonstrated an increase in the haematological parameters (UBR: P < 0.01, LDH: P < 0.05) when compared to athletes who ran on asphalt (UBR: P < 0.05, LDH: P = 0.241). Our findings indicate that intravascular haemolysis occurs significantly after prolonged running. Furthermore, we conclude that uneven grass surface results in greater haemolysis compared to asphalt road.